The Impact of Corporate Characteristics on The Behavior of Asymmetric Cost (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The current study aimed to test the presence of asymmetric cost behavior, specifically sticky cost behavior or anti-sticky cost behavior. and examine the impact of firm characteristics on asymmetric cost behavior. The study population consisted of 10 companies registered in the Damascus Securities Exchange, with some companies being excluded due to the unavailability of complete required data in their published financial statements. During the period from 2007 to 2018, which was the period for which data was available during the data collection phase.    The independent variables resulting from firm characteristics, such as asset intensity and debt intensity, were measured by the ratio of fixed assets and debt to total revenue, respectively. The dependent variable, cost behavior, including administrative, selling, and general costs, was measured by the ratio of costs in the current year to costs in the previous year.      The results showed the presence of sticky cost behavior for administrative, selling, and general costs. There was a positive relationship between fixed asset intensity and sticky cost behavior. There was an inverse relationship between debt intensity and sticky cost behavior.